Novel Aptamer Strategies in Combating Bacterial Infections: From Diagnostics to Therapeutics - Zijian Ye; Huaizhi Chen; Harrie Weinans; Bart van der Wal; Jaqueline Lourdes Rios (MDPI AG, 2024)
Bacterial infections and antimicrobial resistance are posing substantial difficulties to the worldwide healthcare system. The constraints of conventional diagnostic and therapeutic approaches in dealing with continuously changing infections highlight the necessity for innovative solutions. Aptamers, which are synthetic oligonucleotide ligands with a high degree of specificity and affinity, have demonstrated significant promise in the field of bacterial infection management. This review examines the use of aptamers in the diagnosis and therapy of bacterial infections. The scope of this study includes the utilization of aptasensors and imaging technologies, with a particular focus on their ability to detect conditions at an early stage. Aptamers have shown exceptional effectiveness in suppressing bacterial proliferation and halting the development of biofilms in therapeutic settings. In addition, they possess the capacity to regulate immune responses and serve as carriers in nanomaterial-based techniques, including radiation and photodynamic therapy. We also explore potential solutions to the challenges faced by aptamers, such as nuclease degradation and in vivo instability, to broaden the range of applications for aptamers to combat bacterial infections.